The energy metabolism-promoting effect of aconite is associated with gut microbiota and bile acid receptor TGR5-UCP1 signaling - Dandan Zhang; Dandan Zhang; Dandan Zhang; Hao Cheng; Jing Wu; Yaochuan Zhou; Fei Tang; Juan Liu; Wuwen Feng; Wuwen Feng; Cheng Peng; Cheng Peng (Frontiers Media S.A., 2024)
IntroductionAs a widely used traditional Chinese medicine with hot property, aconite can significantly promote energy metabolism. However, it is unclear whether the gut microbiota and bile acids contribute to the energy metabolism-promoting properties of aconite. The aim of this experiment was to verify whether the energy metabolism-promoting effect of aconite aqueous extract (AA) is related to gut microbiota and bile acid (BA) metabolism.MethodsThe effect of AA on energy metabolism in rats was detected based on body weight, body temperature, and adipose tissue by HE staining and immunohistochemistry. In addition, 16S rRNA high-throughput sequencing and targeted metabolomics were used to detect changes in gut microbiota and BA concentrations, respectively. Antibiotic treatment and fecal microbiota transplantation (FMT) were also performed to demonstrate the importance of gut microbiota.ResultsRats given AA experienced an increase in body temperature, a decrease in body weight, and an increase in BAT (brown adipose tissue) activity and browning of WAT (white adipose tissue). Sequencing analysis and targeted metabolomics indicated that AA modulated gut microbiota and BA metabolism. The energy metabolism promotion of AA was found to be mediated by gut microbiota, as demonstrated through antibiotic treatment and FMT. Moreover, the energy metabolism-promoting effect of aconite is associated with the bile acid receptor TGR5 (Takeda G-protein-coupled receptor 5)-UCP1 (uncoupling protein 1) signaling pathway.ConclusionThe energy metabolism-promoting effect of aconite is associated with gut microbiota and bile acid receptor TGR5-UCP1 signaling.